Fist Report of Stiphodon atropurpureus (Herre, 1927) in Marente Village, Sumbawa, West Nusa Tenggara - Arung Mulya; Sania Citra; Ari Okta Andini; Rasali Abdur rahman; Win Ariga; Sagita Cahyani; Izzul Islam; Veryl Hasan (Journal of Aquaculture and Fish Health, 2023)
Marente is a village at the foot of the ancient Sumbawa volcano, located on the Tiu Kele river and the Agal waterfall, which empties directly into the sea. The ecological condition of the Tiu Kele river is an ideal environment for Stiphodon fish to live and breed. Therefore, this study focused on identifying the species of Stiphodon sp. (Gobiidae), whose presence has not been recorded in West Nusa Tenggara. There is still no literature study related to the Gobiidae family, especially the genus Stiphodon in the waters of the Tiu Kele river, which makes this research very important to do. This research was conducted from September 13 to October 13, 2021, in Tiu Kele river, Marente village, Sumbawa. The tools used are net, dipper, aquarium, sampling tubes, thermometer, pH meter, and camera, while the material used is 96% alcohol for specimen preparation. The identification results stated that Stiphodon atropurpureus had clearly visible characteristics. It had a bright blue body from the snout and cheeks to the tail, the dorsal fin is separated and fibrous. These results were also later strengthened from various related references about the physical properties and characteristics of Stiphodon atropurpureus. The results of this research can later be used as a reference and new data related to the distribution of stiphodon in Indonesia, especially in Lesser Sunda.